2015
DOI: 10.1007/s13524-014-0361-2
|View full text |Cite
|
Sign up to set email alerts
|

Legal Recognition of Same-Sex Couples and Family Formation

Abstract: It has long been debated how legalizing same-sex marriage would affect (different-sex) family formation. In this article, I use data on OECD member countries for the period 1980-2009 to examine the effects of the legal recognition of same-sex couples (through marriage or an alternative institution) on different-sex marriage, divorce, and extramarital births. Estimates from difference-in-difference models indicate that the introduction of same-sex marriage or of alternative institutions has no negative effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 39 publications
4
25
0
Order By: Relevance
“…15 Therefore, this null result from such a placebo test reinforces the validity of the main analysis. This finding is also in line with the work of Badgett (2009), Francis et al (2012), and Trandafir (2015) highlighting that SSM legalization did not affect heterosexual behavior. In other words, as also discussed in the Introduction, there is no evidence that SSM led to a deterioration of the American family.…”
Section: Placebo Testssupporting
confidence: 89%
See 1 more Smart Citation
“…15 Therefore, this null result from such a placebo test reinforces the validity of the main analysis. This finding is also in line with the work of Badgett (2009), Francis et al (2012), and Trandafir (2015) highlighting that SSM legalization did not affect heterosexual behavior. In other words, as also discussed in the Introduction, there is no evidence that SSM led to a deterioration of the American family.…”
Section: Placebo Testssupporting
confidence: 89%
“…Homosexuality is illegal or barely tolerated in most countries outside Western Europe and North America. Previous research have pointed out that there is no effect of SSM legalization on heterosexual behavior (Badgett, 2009), including non-marital sex (Francis et al 2012), marriage, divorce and extramarital birth rates (Dillender, 2014;Trandafir, 2015), thus dispelling any concerns about the potential destruction of traditional family values. This paper shows instead that a more tolerant environment can increase participation of gay and lesbian individuals in the labor market, thus offering an additional economic justification to the expansion of LGBT rights.…”
Section: Introductionmentioning
confidence: 99%
“…Our article adds to a small but growing literature on marriage-like contracts for same-sex couples afforded by the recent expansion of such rights (Burn and Jackson 2014;Carpenter and Gates 2008;Dillender 2014Dillender , 2015Langbein and Yost 2009;Trandafir 2015). Exploiting cross-sectional and time variation, a number of studies have found no evidence of the legalization of same-sex unions eroding traditional values as measured by marriage, divorce, or abortion rates.…”
Section: Introductionmentioning
confidence: 86%
“…4 For the United States, see Langbein andYost (2009) andDillender (2014). For the OECD, see Trandafir (2015). 5 Syphilis is a sexually transmitted disease that is "relatively common among men who have sex with men" (Dee 2008(Dee :1056.…”
Section: Introductionmentioning
confidence: 99%
“…More recently the focus has altered to considering various aspects of same-sex partnership or marriage. The impacts on opposite-sex marriage rates and fertility have been examined (Dillender, 2014;Trandifir, 2015), as have those on employment (Burn (2018) ;Delhommer, 2019;Sansone, 2020); partners' labor supply and household bargaining (Oreffice, 2011;Hansen et al, 2019), including effects of taxation (Isaac, 2018); and even on mental health (Anderson et al, 2019) and sexually transmitted diseases (Francis et al, 2012). 1 All of these considerations are important in understanding the position of this particular minority group in American society and generally.…”
Section: Introduction and The Problemmentioning
confidence: 99%